2005
DOI: 10.1097/01.jcp.0000185425.00644.41
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment With Sulpiride and Paroxetine for Accelerated Response in Patients With Major Depressive Disorder

Abstract: Although serotonin reuptake inhibitors are recommended as first-line agents for major depressive disorder, delayed onset of action is problematic, and faster effective treatment is needed. Sulpiride, a dopamine-mediated agent, has been reported to show faster antidepressant efficacy, and we examined the efficacy of adjunctive sulpiride in combination with paroxetine (PAX), compared with PAX alone, to clarify whether the combined treatment exerts faster effect. Forty-one major depressive disorder patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…All of these D2R antagonists also appear to interact with other neurotransmitter receptors and at multiple sites in reducing depression and psychosis in humans. 28 These mixed results in relation to FDM likely reflect the complexity of D2R actions in the retina, depending on different basal DA levels and the partial specificity of many D2R drugs. Therefore, the exact role of D2R in the development of FDM remains to be critically evaluated.…”
mentioning
confidence: 98%
“…All of these D2R antagonists also appear to interact with other neurotransmitter receptors and at multiple sites in reducing depression and psychosis in humans. 28 These mixed results in relation to FDM likely reflect the complexity of D2R actions in the retina, depending on different basal DA levels and the partial specificity of many D2R drugs. Therefore, the exact role of D2R in the development of FDM remains to be critically evaluated.…”
mentioning
confidence: 98%
“…The finding suggests that adjunctive sulpiride may be safely withdrawn in remitted depression. Taken together with the findings in the published reports, 1 although the adjunctive antipsychotic treatment may enhance antidepressant effects, discontinuation of an additional antipsychotic drug may need to be considered in remitted patients with major depressive disorder. These preliminary findings should be tested in larger samples.…”
mentioning
confidence: 64%
“…WHILE ANTIPSYCHOTICS ARE suggested to be useful as an augmentation strategy for the treatment of depression, 1 they are also associated with metabolic disturbances such as prolactin elevation, which could result in amenorrhea and decreased bone density 2 . This notwithstanding, few studies have evaluated the effects of their discontinuation after achieving remission, which is the goal of treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, other authors 8,10 have reported prolactin elevation with low-dose amisulpride. Prolactin elevation has also been reported with low doses of sulpiride 9,12 and levosulpiride. 7 Finally, dose-dependent prolactin elevation and greater prolactin elevation in women than in men has been described with other antipsychotic drugs, such as paliperidone, as well.…”
Section: -11mentioning
confidence: 83%